Above and below ground plant inputs and soil organic matter cycling in an eucalypt plantation in the cerrado biome - Teixeira, Rafael da Silva (2017)
Soil organic matter (SOM) plays key roles on high productive agrosystems, further may offer an alternative to reduce soil CO 2 -C emissions and improve soil C sequestration. In Brazil, most of the Cerrado (Brazilian Savannah) were initially converted to pastures using unsustainable practices, which promoted soil degradation, soil organic carbon (SOC) stocks losses and increase in GHG emissions. Thus, the conservation land-management systems that favor the input of aboveground and belowground plant residue-C to soil may reduce the impacts caused by land-use change. Because eucalypt trees are fast-growing, they are attractive for C sequestration (aboveground and belowground) and subsequent C input to the soil. So, eucalypt plantation may sequester C in compartments with different timescales: i) Plant biomass and ii) Soil organic matter (SOM). So, this thesis aimed to study the C and N dynamics, focusing in the processes that underline CO 2 -C emissions in on eucalypt plantation since the land-use change following a pasture, until 4-years-old. We report our research in three chapters, aimed at understanding some research gaps. In the first chapter we analyzed the changes in C and N stocks, CO 2 -C and CH 4 -C fluxes in Cerrado, pasture (cultivated for 34-years following the clearing of the Cerrado) and eucalypt (cultivated for 4 years following the pasture). The soil surface CO 2 -C, CH 4 -C fluxes and also CO 2 -C concentration along the vertical soil profile were measured in different seasons (Wet and Dry) over three years. It was also determined the C and N stocks associated to the particulate organic matter (POM) and mineral-associated organic matter (MAOM). Variation in natural abundance of 13 C (δ 13 C) was used to partition the SOM in old (Cerrado- or pasture-derived) and their replacement by the new input C (eucalypt-derived). It was observed that the wet season had the strongest influence on soil surface CO 2 -C and CH 4 -C fluxes, and CO 2 -C concentration at soil depths for the different land uses. The soil under eucalypt plantation emitted ~70% more CO 2 -C than those under Cerrado and pasture after 40-months of eucalypt planting, while the pasture soil emitted more CH 4 -C to the atmosphere than those under Cerrado and eucalypt in Sep 2012, Jan 2013 and Oct 2015. The old MAOM-C losses in deep soil layers were not compensated by the new eucalypt C inputs, resulting in net soil C losses. Nevertheless, no differences were detected to POM-C and -N in the soil (0.0-1.0 m), perhaps indicating a recovery in SOM in eucalypt stands at a more advanced stand age. In the second chapter, we investigated de dynamics of CO 2 -C components in soil surface and soil profile, also tracking the influence of eucalypt root growth (especially fine roots) on these processes. Due historical use was possible partition the soil surface CO 2 -C flux and the CO 2 -C concentration in depth in CO 2 -C plant-derived and CO 2 -C soil-derived. In addition, the root priming effect was calculated. The evaluations were carried out in six seasons: 3, 7, 15, 19, 31 and 40-month-old eucalypt. After the implantation of eucalypt forests there was an increase in soil surface CO 2 -C flux along plant growth (4.33 kg ha -1 h -1 in 40 month-old eucalypt). The root growth contributes greatly to the soil surface CO 2 -C flux (correlated at p<0.01; r: 0.61) promoting the surface RPE over time (correlated at p<0.01; r: 0.63). The moisture has greater influence in the decomposition of litterfall (correlated at p<0.01; r: 0.70) and root respiration and/or rhizodeposition decomposition (correlated at p<0.01; r: 0.79). Finally, in the third chapter we accessed the biomass C storage (Leaves, branches, barks, woods, fine roots, medium roots and coarse roots) and C storage in different SOM pools (POM and MAOM) over time. Eucalypt forest at 36-months-old allocated 72.01 Mg ha -1 of C, with 41.5% being directed to the roots (29.92 Mg ha -1 of C). After 49-months of planting there were mineralization in POM-, MAOM-Cerrado and Pasture, providing an estimated N mineralization of 0.535 Mg ha -1 in the 0.0-1.0-m layer. In contrast, the root-derived C imputed to soil was more efficient in soil organic matter formation (58% higher) than the litterfall- + root-derived C imputed to soil. After 49-months of eucalypt planting the forest was not a potential sequestration of C (ΔC Soil : -2.22 Mg ha -1 ) to 0.0-1.0 m soil layer. However, studies with longer time scales are required for completeness of information about potential of CO 2 -C sequestering by eucalypt forest.